Interactive Digital Design: Synergy between Artificial Intelligence, Art, Design and Architecture - Roude, Jessica Anahí (2024)
This paper examines the intersection of Artificial Intelligence (AI) and interactive 3D digital design technologies within the domains of art, design, and architecture in Latin America. It explores how these technologies not only optimize creative processes but also serve as co-creators, reshaping interactions between professionals, creations, clients, and work environments. Grounded in frameworks such as boundary objects and Actor-Network Theory, the study investigates AI platforms' role in fostering collaboration between human and non-human actors, mediating aesthetic and functional decisions in creative projects. Through case studies from Brazil, Colombia, Uruguay, and Argentina, this research highlights opportunities for innovation in sustainability, urban design, and immersive experiences, alongside challenges such as economic constraints, inadequate infrastructure, and limited professional training. The findings suggest that while AI and 3D technologies unlock significant creative potential, their effective adoption requires addressing these systemic barriers.